Mengenal pengaruh media sosial terhadap perkembangan fashion hijab di kalangan perempuan muslimah - Abdallillah, Najwa Aisyah (Maliki Interdisciplinary Journal, 2024)
The phenomenon of using hijab today has shifted from the true meaning of hijab. The essence of hijab is worn as a cover of aurat in Islam for women, but now most of the meaning of hijab is interpreted as a fashion. With the development of social media today, it finally affects a person’s mindset in wearing hijab as a form of self-identity of a Muslim woman. The order of hijab has also changed to be more fashionable and stylist. The rapid development of hijab style through social media has encouraged many women, especially young people, to continue to express their identity and religion in their daily lives. The purpose of this research is to see the role of social media in influencing the current hijab fashion among women. The approach in this research uses a qualitative approach with descriptive analysis method, which is by examining and trying to solve problems that are currently happening. In addition, the author here also tries to conclude that social media is one of the tools that greatly influences as well as a channel for hijab fashion icons in expressing their creativity in modern hijab fashion arrangements and in accordance with Islamic religion.